Penguasaan Kosakata Bahasa Jerman - Melani, Patricia; Saleh, Nurming; Usman, Misnawaty (Universitas Negeri Makassar, 2024)
Abstract. This research is descriptive research with a quantitative approach. This research aims to determine the level of mastery of German vocabulary in class XI SMA Negeri 8 Gowa and the factors that influence it. The population in this study were all students in class XI IPS 1, IPS 2, and IPS 3, SMA Negeri 8 Gowa. The sample in this study was class XI IPS 1 students, totaling 32 students using random sampling techniques. The data of this research was obtained from language vocabulary mastery tests and questionnaires. Technique analysisof the data was carried out using percentage techniques. Based on the results of data analysis, it was concluded that the German vocabulary mastery of Class XI students at SMA Negeri 8 Gowa was in the sufficient category (66%). The influence factors these results are internal factors and external factors. Keywords: Mastery of vocabulary, internal factors, external factors